The current perspective transformation ontoepistémica education of special education mode (Revista Electrónica REDINE, 2018)
Special education in Venezuela has adopted various educational policies and models of care, who have outlined actions to provide specialized education according to the needs and interests of learners. Different models have prevailed over time, as the clinician, who focused on the organic and behavioral educationally but then took the first steps to provide this population with more educational approach than clinical. The social humanist model has prevailed in recent years, educational policy being adopted as from 1997, as a consequence consolidated campuses services and special education mode, however, after 14 years there has been a transformation in the care of this population so it is worth pondering because of resistance found in those who are the protagonists of pedagogical.
Keywords: functional diversity; humanism; inclusion